Somewhat original: energy ethics in Malawi's off-grid solar market. Issue 3 (3rd July 2021) - Samarakoon, Shanil; Bartlett, Anne; Munro, Paul
ABSTRACT: Solar products are increasingly framed as being integral to addressing energy poverty in the Global South. This is especially the case in sub-Saharan Africa where the promise of centralized grids has given way to an emphasis on off-grid market-based solutions. While these solutions promise much, the quality and originality of these products is often contested. In this paper, we draw upon ethnographic insights from Malawi's solar market to examine the energy justice implications of this deepening reliance on markets to provide energy for poor populations with no access to electricity. Specifically, we examine the ethics and implications of 'somewhat original' solar – an amorphous product category that constitutes the vast majority of solar products sold in the Global South. Analysing Malawi's solar market, this paper illustrates how moral claims about off-grid solar products often sit incongruously with the realities of global supply chains and poor market regulation. We conclude that while off-grid solar products offer the energy poor some respite from darkness, they are, nonetheless, commodities that are prone to reproducing structural forms of injustice and do not, always, represent a sustainable solution to energy poverty in the Global South.